AUDIT SPECIALIST, PERUBAHAN MANAJEMEN, DAN KARAKTERISTIK PERUSAHAAN TERHADAP AUDITOR SWITCHING - Christina Devi; Muhammad Arief Effendi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study to examine and obtain an empirical evidence the influences of auditor firm reputation, financial distress, management change, prior audit opinion, profitability, client company size, audit delay, and industry specialization on auditor switching. The data used in this study is a secondary data which is collected from the non-financial company’s audited financial statements that is listed on the Indonesia Stock Exchange for period 2016-2019. The method used is purposive sampling and resulted in 119 companies that matched with the criteria stated. Logistic regression is used as the data analysis method in this study. The result shows that auditor firm reputation has negative influence on auditor switching, which means the company audited by BIG 4 tend to not do auditor switching.